Assessment of professionalism: From where have we come – to where are we going? An update from the Ottawa Consensus Group on the assessment of professionalism. (4th March 2019) - Hodges, Brian; Paul, Robert; Ginsburg, Shiphra; the Ottawa Consensus Group Members,
Abstract: Background: In 2009, an International Working Group (IWG) on the Assessment of Professionalism began collaborating and published recommendations in 2011. Nearly a decade later the IWG reconvened to take stock of the state of practice and research in professionalism and the impact of the 2011 report. Method: A bibliometric study identified all publications on assessment of professionalism since 2011, noting those that cited the original report. Articles were coded to identify the reason for citation and new trends in assessment. Bibliometric data were supplemented by discussion groups held at key international education meetings. Results: Six-hundred publications on the assessment of professionalism were found in Google Scholar and 164 in Web of Science since 2011, of which 177 (30%) and 84 (50%) respectively cited the original IWG publication. English language publications were most common (83%), but there were articles in 13 other languages by authors from 40 countries. The report was cited commonly to justify attention to professionalism in general (41%), assessment of professionalism (38%) and to explore professionalism in different countries and professions (25%). A thematic analysis showed that of 9 research areas recommended in 2011, 7 of 9 categories were represented with a large increase in research across languages and cultures. Conclusions: Though the assessment of professionalism remains a challenge the research base continues to grow, especially related to professionalism across cultures and languages, and a large percentage of publications cite the IWG recommendations. There remains a gap in research and writing about patients' perspectives.